Morphometric characters and length-weight relationship of Bele, (Glossogobius giuris) from Mithamoin haor, Kissorgonj, Bangladesh - Hossain, MS; Sultana, N (Journal of the Bangladesh Agricultural University, 2016)
Different morphometric characters such as total length (TL), standard length (SL), head length (HL), eye diameter (ED), body depth (BD), pre-orbital length (POL) were measured on Glossogobius giuris collected from Mithamoin haor showed that percentage growth value of SL, BD, HL, ED and POL were higher in female. A linear relationship was found between total length and morphometric characters and these also showed significant positive correlation (p<0.001) between dependent and independent variables. The length-weight relationships of G. giuris were calculated for males, females. The relationship was analyzed using the formula W=aLb after transform into straight-line equitation. The equation obtained for male was; Log W = 2.757 Log TL 1.757; for female; Log W = 2.843 Log TL 1.868. The regression coefficients (b) between males and females did not show any significant difference (p>0.05) while b value significantly deviated from the expected cube value of 3 in case of male only thus indicating negative allometry. However, relative condition factor (Kn) of G. giuris computed for female was 1.009 ± 0.124 and for male was 1.016 ± 0.199, which suggest the specimen were healthy and in good condition. All this variation between male and female may be due to spawning cycle or other physiological activities or environmental factors. J. Bangladesh Agril. Univ. 12(2): 389-395, December 2014